The effectiveness of Stimulating Neural Branching Strategies on mental alertness among second-grade intermediate students in science - Muhsin, Helen Sarhan; Madhi Al-Ibadi, Mustafa Lafta (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to identify the effectiveness of Stimulating Neural Branching Strategies on mental alertness in intermediate second-grade students in the subject of science, and to achieve the goal of the research, the researchers used the experimental method with partial control, through the following null hypothesis: There is no statistically significant difference at the level of significance (0.05) Between the average scores of the experimental group students who will study using strategies that stimulate the nerve bifurcation and the average scores of the control group students who will study in the usual way in mental alertness, the research sample consisted of (54) students, and each group had (27) students, and the two groups were rewarded, and to verify the research hypothesis The two researchers prepared the mental alertness scale (32 items) and their validity and reliability were verified and applied after the end of the experiment, and the results showed statistically significant differences between the mean scores of the mental alertness scale for the experimental group students and the control group students and in favor of the experimental group students. In the light of the results, the two researchers concluded the effectiveness of strategies that stimulate the nerve branching on mental alertness among second-grade intermediate students in the science subject.